Kajian Penggunaan Matriks Pada Formulasi Tablet Lepas Lambat: Artikel Review - Tarizza Puspa Anggrelia; Amelia Saputri Ginting; Yeka Khafidz Illa Rosyidah; Maratul Istifadah; Faizal Agustino; Dewi Rahmawati; Yani Ambari; Marthy Meliana Ariyanti Jalmav; Muhammad Fithrul Mubarak (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
This research discusses the use of matrices in sustained-release tablet formulations to optimize the active substance release profile. Extended-release tablets are a type of tablet formulation designed to release the active substance gradually in the body over a certain period of time. The main purpose of sustained-release tablets is to maintain drug levels in the blood or target area over a longer period of time, compared to conventional tablets which release the active substance quickly after ingestion. The method used in this research is a qualitative approach which aims to deepen an in-depth understanding of the phenomenon being studied. As a result, selecting the right type of matrix proves to be crucial in achieving the expected therapeutic effectiveness. Polymer matrices, both natural and synthetic, play an important role in controlling the stability and efficiency of tablets and their ability to gradually release active substances.